Of popular wisdom : indigenous knowledge and practices in Bangladesh - Khan, Niaz Ahmed, 1966-; Sena, Sukānta, 1965-; Bangladesh Resource Centre for Indigenous Knowledge (Dhaka : Bangladesh Resource Centre for Indigenous Knowledge, 2000)
Contributed articles.
Includes bibliographical references.
Keywords: Rural development -- Bangladesh; Ethnoscience -- Bangladesh